Human rights and social justice : fundamental rights vis-a-vis directive principles - Sharma, Gokulesh, 1958- (New Delhi : Deep & Deep publications, 1997)
Chiefly with reference to India.
Dr.Rohimi/Rastech
Includes bibliographical references (p. [497]-500) and index.
Keywords: Civil rights -- India; Human rights -- India; Social justice